Analisis Hukum Pertanggungjawaban Pelaku Doxxing terhadap Pelanggaran Hak Privasi di Media Digital - Richard Anggiat Oloan; Aturkian Laia (INDO PUBLISHING, 2026)
Doxxing is the unauthorized gathering and dissemination of personal data in digital media to intimidate victims, yet the term remains unregulated under a standalone legal norm in Indonesia. This normative juridical research aims to analyze doxxing as a privacy violation, the perpetrator's legal liability, and regulatory effectiveness using statutory, conceptual, and case approaches. The results indicate that doxxing is qualified as a multi-layered criminal offense scattered across the Criminal Code (defamation), the Personal Data Protection Law (Article 65 juncto Article 67), and the Electronic Information and Transactions Law (Article 26). Criminal liability is cumulative-alternative, while victim recovery can be pursued through criminal channels, civil lawsuits for unlawful acts, or administrative sanctions. However, its effectiveness is hindered by fragmented norms, difficulties in digital evidence gathering, and perpetrator anonymity. This study recommends regulatory harmonization and capacity-strengthening for cyber law enforcement to ensure legal certainty for citizens' privacy rights in the digital space.